Hubungan Sosiodemografi Pasien dengan Pengetahuan Pasien tentang Pelayanan Informasi Obat menggunakan Telefarmasi (E-Pharmacy) - Mita Restinia; Mabrurotul Mustafidah; Rania Adhamira; Annisa Putri Kinanti (UIN Syarif Hidayatullah Jakarta, 2024)
E-pharmacy or telepharmacy is a form of ICT-based health service that facilitates consultation with medical practitioners. Telepharmaceutical services in Indonesia have not been implemented widely. This is because ICT access has not been perfectly spread throughout Indonesia. There is also still little socialization related to telepharmaceuticals, so that the understanding of telepharmaceuticals cannot reach the public, which causes telepharmaceuticals to not being implemented properly. This study aims to determine the relationship between the sociodemographic characteristics of respondents and the level of patient knowledge of drug information services using telepharmacy. This research is a descriptive quantitative correlation research. Respondents in this study amounted to 401 people. Statistical test using Chi Square test obtained p value < 0.05 for age and education test with telepharmaceutical knowledge, which can be concluded that there is a relationship between respondent's age and education with telepharmaceutical knowledge; and p value > 0.05 for the test of gender, occupation, frequency of application use with telepharmaceutical knowledge, which can be concluded that there is no relationship between gender, occupation, frequency of application use and telepharmaceutical knowledge.